"Ubuntu philosophy" for public leadership and governance praxis: Revisiting the ethos of Africa's collectivism. Issue 4 (23rd October 2019) - Asamoah, Kwame; Yeboah-Assiamah, Emmanuel
Abstract : Purpose: Leadership and governance are all about "people" and the "common welfare". Africans have an Ubuntu philosophy which culturally calls on individuals to promote the welfare of collective society. It is therefore paradoxical to note how African leaders and governance regimes perform poorly when it comes to the usage of public resources to create conditions for collective human welfare. Why do leaders instead of championing societal advancement rather advance their selfish, egoistic and sectional interests? This study aims to unpack a prevalent paradox and discuss a new approach of linking the rich Ubuntu philosophy to Africa's governance and leadership discourse. Design/methodology/approach: This study discusses from secondary sources of data, mainly drawn from journal articles, internet sources and scholarly books relevant to leadership and public administration in developing African countries and how Ubuntu African philosophy can be deployed to ensure leadership ethos. In attempt to obtain a more comprehensive and systematic literature review, the search covered all terms and terminologies relevant to the objective of the study. The search process mainly comprised four categories of keywords. The first category involved the concept as approximately related to leadership: "leadership and civic culture", "Ubuntu culture" and "African collectivist culture". For the final category, words such as "crisis", "failure" and "experiences" were used. Findings: This study contends that the preponderance of corruption and poor leadership in Africa is anti-cultural, anti-human, anti-ethical and anti-African; hence, those individuals who indulge or encourage leadership paralysis are not "true Africans" by deeds but merely profess to be. Linking the African Ubuntu philosophy to public leadership, the study maintains that the hallmark of public leadership and governance is to develop the skills of all and caring for the society. Practical implications: This study draws attention to the need for leaders to espouse virtues so that leadership becomes a tool to promote societal welfare. The hallmark of public leadership and governance is to develop the skills of all and caring for the society. It involves weighing and balancing professional and legal imperatives within a democratic and ethical context with an ultimate responsibility to the people and public interest. It is not a responsibility to a particular set of citizens, but a commitment to be just and equitable to all. The preponderance of corruption and bad leadership is anti-cultural, anti-human, anti-ethical and anti-African; hence, individuals who indulge or encourage leadership paralysis are not true Africans by deeds but merely profess to be. Originality/value: This study draws a clear link between indigenous African cultural value system and ethical public leadership. It draws congruence between Africa's Ubuntu philosophy of civic virtue and Africa's leadership/governance. This will bring about a renewal of thoughts and practice of public leadership on the continent, as it has been demonstrated that a true African seeks collective social welfare and not selfish interest.